2014
DOI: 10.1128/microbiolspec.ehec-0012-2013
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Response during Enterohemorrhagic Escherichia coli Infection

Abstract: The inflammatory response is an integral part of host defense against enterohemorrhagic Escherichia coli (EHEC) infection and also contributes to disease pathology. In this article we explore the factors leading to inflammation during EHEC infection and the mechanisms EHEC and other attaching and effacing (A/E) pathogens have evolved to suppress inflammatory signaling. EHEC stimulates an inflammatory response in the intestine through host recognition of bacterial components such as flagellin and lipopolysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 130 publications
0
22
0
Order By: Relevance
“…EPEC also encodes a vast repertoire of non-LEE-encoded effectors that are not directly involved with cytoskeleton remodeling but instead play an important role in the modulation of host inflammatory response during the course of infection (20)(21)(22)(23)(24)(25)(26)(27). These effectors are highly conserved among AE pathogens and are generally encoded by genomic islands, suggesting that the acquisition of these elements was necessary to attenuate the inflammatory response triggered by EPEC's interaction with the host cell.…”
mentioning
confidence: 99%
“…EPEC also encodes a vast repertoire of non-LEE-encoded effectors that are not directly involved with cytoskeleton remodeling but instead play an important role in the modulation of host inflammatory response during the course of infection (20)(21)(22)(23)(24)(25)(26)(27). These effectors are highly conserved among AE pathogens and are generally encoded by genomic islands, suggesting that the acquisition of these elements was necessary to attenuate the inflammatory response triggered by EPEC's interaction with the host cell.…”
mentioning
confidence: 99%
“…There is mounting evidence that EPEC inhibits the transcriptional responses of the IEC to which it is attached, effectively shutting down the TNF signaling pathway (Pearson and Hartland 2014). EPEC attacks TAB2 and TAB3, which are adaptors for TAK1 downstream from RIPK1.…”
Section: Epec Triple Attacks Transcription Apoptosis and Necroptosismentioning
confidence: 99%
“…Tarr and coauthors review in chapter 15 (58) the clinical features of STEC infections in humans, including outcomes and prognosis, and provide insights from both gastroenterological and nephrological perspectives. The inflammatory response to STEC infection and the virulence factors these pathogens have evolved to thwart this response are discussed by Pearson and Hartland in chapter 16 (85). Unfortunately, no ideal therapy is available for STEC infections, and the use of antimicrobials is contraindicated, at least for typical EHEC infections, although investigators of the German O104:H4 outbreak reported the benefit of azithromycin treatment to reduce fecal shedding of the organism.…”
Section: The Presentmentioning
confidence: 99%